Brief Report: Modeling the Impact of Voluntary Medical Male Circumcision on Cervical Cancer in Uganda. (1st March 2021) - Davis, Stephanie M.; Habel, Melissa A.; Pretorius, Carel; Yu, Teng; Toledo, Carlos; Farley, Timothy; Kabuye, Geoffrey; Samuelson, Julia
Abstract : Background: In addition to providing millions of men with lifelong lower risk for HIV infection, voluntary medical male circumcision (VMMC) also provides female partners with health benefits including decreased risk for human papillomavirus (HPV) and resultant cervical cancer (CC). Setting: We modeled potential impacts of VMMC on CC incidence and mortality in Uganda as an additional benefit beyond HIV prevention. Methods: HPV and CC outcomes were modeled using the CC model from the Spectrum policy tool suite, calibrated for Uganda, to estimate HPV infection incidence and progression to CC, using a 50-year (2018–2067) time horizon. 2016 Demographic Health Survey data provided baseline VMMC coverage. The baseline (no VMMC scale-up beyond current coverage, minimal HPV vaccination coverage) was compared with multiple scenarios to assess the varying impact of VMMC according to different implementations of HPV vaccination and HPV screening programs. Results: Without further intervention, annual CC incidence was projected to rise from 16.9 to 31.2 per 100, 000 women in 2067. VMMC scale-up alone decreased 2067 annual CC incidence to 25.3, averting 13, 000 deaths between 2018 and 2067. With rapidly-achieved 90% HPV9 vaccination coverage for adolescent girls and young women, 2067 incidence dropped below 10 per 100, 000 with or without a VMMC program. With 45% vaccine coverage, the addition of VMMC scaleup decreased incidence by 2.9 per 100, 000 and averted 8000 additional deaths. Similarly, with HPV screen-and-treat without vaccination, the addition of VMMC scaleup decreased incidence by 5.1 per 100, 000 and averted 10, 000 additional deaths. Conclusions: Planned VMMC scale-up to 90% coverage from current levels could prevent a substantial number of CC cases and deaths in the absence of rapid scale-up of HPV vaccination to 90% coverage.